Adsorbent cartridge with long shelf life
By optimizing the layered structure of the adsorbent box, the water content difference between zirconium phosphate/zirconia/activated carbon layers is minimized, and the problem of layer separation and unevenness of the adsorbent box during storage is solved, and long-term storage stability is achieved and efficient toxin removal effect.
Patent Information
- Application Number
- CN202380039742.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-19
- Filing Date
- 2023-05-18
- Publication Date
- 2025-02-18
AI Technical Summary
During storage, existing adsorbent cartridges are prone to separation or cracking of adsorbent layers, resulting in uneven water content, affecting the filtration efficiency of the dialysate and removing the adsorbent, thereby reducing the therapeutic effect.
By optimizing the layered structure of the adsorbent box, ensure that the water content difference between the zirconium phosphate/zirconia/activated carbon layers is minimal, usually less than or equal to 8 wt.%, for stable storage for at least 8 weeks, or even longer.
The long-term storage stability of the adsorbent box is achieved, interlayer separation and inhomogeneity are avoided, the dialysate filtration efficiency and the ability of adsorbent to remove toxins are improved, and the shelf life is extended.
Smart Images

Figure BDA0005128128870000061 
Figure BDA0005128128870000121 
Figure BDA0005128128870000122
Abstract
Description
Technical Field
[0001] The invention relates to an adsorbent box with a long shelf life. By providing the layered adsorbent, the minimum difference in water content between layers is achieved, thereby improving the shelf life. Background Art
[0002] The listing or discussion of a previously published document in this specification must not necessarily be taken as an admission that the document is part of the state of the art or is common general knowledge.
[0003] Adsorbents are used in renal dialysis, especially to remove toxins from the dialysate. Adsorbent cartridges are composed of various components, such as ion exchangers such as zirconium phosphate (ZP) and hydrous zirconium oxide (HZO); activated carbon (AC); urea toxin removal component (immobilized) urease, etc. The various components in the adsorbent are usually provided in the form of different layers. The adsorption cartridge containing the adsorbent is called an adsorbent cartridge.
[0004] Patients who require dialysis often choose to receive overnight treatment at home, as this allows them to lead a relatively normal life during the day and avoid frequent trips to a dialysis center. To do this, patients need to store their dialysis equipment and all necessary dialysis materials, such as dialysate and sorbent cartridges, at home. Being able to store these components long-term is a convenience for patients, as bulk deliveries can be made less frequently.
[0005] One problem associated with layered sorbent cartridges is that the sorbent layers may separate or crack, and other defects or inhomogeneities may develop in the sorbent during storage (e.g., as short as two weeks). Gaps formed by separation or cracking of the sorbent layers and any defects or inhomogeneities can severely affect the dialysate flowing through the sorbent, thereby reducing the effectiveness of the sorbent in removing toxins from the dialysate and affecting the therapeutic effect.
[0006] Therefore, there is a need for an adsorbent cartridge that is storage stable for at least 8 weeks, and preferably 12 months or longer. Summary of the invention
[0007] The water content of the ion exchange material in the adsorbent plays an important role in the effectiveness of ion exchange. For example, the inventors have found that the ion exchange efficiency of zirconium phosphate and zirconium oxide can be optimized when the water content is about 20-23 wt.% and 35-40 wt.%, respectively. In contrast, the inventors have found that the water content of the activated carbon layer as another core adsorbent component is generally much lower, about 8 wt.%.
[0008] The inventors have surprisingly discovered that when the difference in water content between the zirconium phosphate / zirconium oxide / activated carbon layers in the adsorbent is minimized, the adsorbent is stable for a longer time. This can be achieved without significantly affecting the ion exchange capacity of the adsorbent. Without being bound by theory, it is believed that substantial differences in water content can cause adsorbents with adjacent zirconium phosphate / zirconium oxide / activated carbon layers to separate during long-term storage, and therefore, minimizing such differences can avoid the above problems.
[0009] Therefore, the present invention provides the following numbered claims.
[0010] 1. The adsorbent box includes:
[0011] a first layer consisting of activated carbon;
[0012] a second layer directly in contact with the first layer, the second layer consisting of one or both of hydrated zirconium oxide and zirconium phosphate,
[0013] in:
[0014] The moisture content of the first layer is X wt.%;
[0015] The moisture content of the second layer is Y wt.%;
[0016] The difference in moisture content between the first layer and the second layer is less than or equal to 8 wt.%.
[0017] 2. The sorbent cartridge of claim 1, wherein the second layer is composed of hydrated zirconium oxide and zirconium phosphate.
[0018] 3. The sorbent cartridge of claim 2, wherein the second layer is comprised of a homogeneous mixture of hydrous zirconium oxide and zirconium phosphate.
[0019] 4. The sorbent cartridge according to claim 1, wherein:
[0020] The second layer is composed of one of zirconium phosphate and hydrated zirconium oxide;
[0021] The adsorbent cartridge further comprises a third layer, the third layer being composed of another zirconium phosphate and hydrated zirconium not present in the second layer;
[0022] The moisture content of the third layer is Z wt.%;
[0023] The difference in moisture content between the second layer and the third layer is less than or equal to 8 wt.%.
[0024] 5. The adsorbent box according to claim 4 is configured so that the dialysate first passes through the zirconium phosphate layer and then passes through the hydrated zirconium oxide layer when in use.
[0025] 6. The sorbent cartridge according to any one of the preceding claims, wherein the difference in moisture content between the first layer and the second layer is less than or equal to 5 wt.%.
[0026] 7. The sorbent cartridge according to claim 6, wherein the difference in moisture content between the first layer and the second layer is less than or equal to 4 wt.%, and optionally less than or equal to 3 wt.%.
[0027] 8. The sorbent cartridge according to claim 4 or 5, wherein the difference in moisture content between the second layer and the third layer is less than or equal to 5 wt.%.
[0028] 9. The sorbent cartridge according to claim 8, wherein the difference in moisture content between the second layer and the third layer is less than or equal to 4 wt.%, and optionally less than or equal to 3 wt.%.
[0029] 10. The sorbent cartridge of any one of claims 4, 5, 8 and 9, wherein the difference between:
[0030] the moisture content of the first layer;
[0031] The weighted average of the moisture content of the second and third layers,
[0032] Less than or equal to 8 wt.%, optionally less than or equal to 5 wt.%, more preferably less than or equal to 4 wt.%, such as less than or equal to 3 wt.%,
[0033] The weighted average of the moisture contents of the second layer and the third layer is based on the mass of hydrated zirconium oxide and the mass of zirconium phosphate.
[0034] 11. The sorbent cartridge according to any one of the preceding claims, wherein the moisture content of the first layer is between 20-35 wt.%, optionally between 23-30 wt.% or between 25-35 wt.%.
[0035] 12. The sorbent cartridge according to any of the preceding clauses, wherein the moisture content of the second layer is between 20-35 wt.%, optionally between 23-30 wt.%, or between 25-35 wt.%.
[0036] 13. The sorbent cartridge according to any one of claims 4, 5 and 8 to 12, wherein the moisture content of the third layer is between 20-35 wt.%, optionally between 23-30 wt.% or between 25-35 wt.%.
[0037] 14. A sorbent cartridge according to claim 4 or any one of claims 5 and 8-13 (depending on claim 4), wherein the water content of the hydrous zirconium oxide layer is between 25-35 wt.%.
[0038] 15. A sorbent cartridge according to claim 3 or any one of claims 6, 7, 11, 12 or 13 (depending on claim 2) wherein the water content of the second layer consisting of a homogeneous mixture of hydrated zirconium oxide and zirconium phosphate is between 23-30 wt.%.
[0039] 16. The adsorbent cartridge according to any one of the preceding claims, further comprising a urease layer consisting of immobilized urease.
[0040] 17. The sorbent cartridge according to claim 16, wherein the water content of the urease layer is between 17-27 wt.%, such as between 19-25 wt.%, such as between 20-24 wt.%.
[0041] 18. The adsorbent box according to claim 16 or 17, wherein the urease layer is in direct contact with at least one of the first layer, the second layer and the third layer (if any), and the difference in water content between the urease layer and the layers in direct contact with it is less than or equal to 8wt.%, such as less than or equal to 5wt.%, less than or equal to 4wt.% or less than or equal to 3wt.%,
[0042] Optionally, when the sorbent cartridge is in use, it is configured such that the urease layer is located upstream of the zirconium phosphate layer.
[0043] 19. The sorbent cartridge according to any one of the preceding claims, wherein the moisture content of the first layer, the second layer, and the third layer and the urease layer (if present) is determined by loss on drying.
[0044] 20. The sorbent cartridge according to claim 19, wherein the moisture content of the first layer, the second layer, the third layer and the urease layer (if present) is measured by loss on drying at 180-220°C (optionally about 210°C) using a Radwag MA200.3Y moisture analyzer. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 An exemplary structure of a three-layer adsorbent is shown.
[0046] Figure 2 An exemplary structure of a double-layer adsorbent is shown.
[0047] Figure 3 The storage stability test results of Comparative Example 1 are shown.
[0048] Figure 4 The storage stability test results of Example 1 are shown.
[0049] Figure 5 The storage stability test results of Comparative Example 2 are shown.
[0050] Figure 6 The storage stability test results of Comparative Example 2 are shown. DETAILED DESCRIPTION
[0051] As described herein, the binding capacity of ion exchange materials (such as zirconium phosphate and hydrous zirconium oxide) in an adsorbent depends on the water content of the ion exchange material, as shown in Table 1.
[0052]
[0053] Table 1: Binding capacity of ion exchange materials zirconium phosphate and hydrous zirconium oxide
[0054] Activated carbon is a common adsorbent component, and the water content of commercially available activated carbon is about 8 wt.%. This is in stark contrast to the preferred water content of ZP and HZO used in peritoneal dialysis. Without being bound by theory, it can be considered that adsorbent layers composed of commercially available activated carbon, ZP and HZO with ideal water content are prone to cracking or separation during long-term storage (Comparative Examples 1 and 2). "Cracking" and "separation" as used herein refer to gaps or air pockets formed in previously dense solid powders, whether vertically, horizontally, or at any angle in between. These gaps or air pockets may be formed between different adsorbent layers, or within the adsorbent layers,
[0055] The present invention solves the problems associated with the prior art. Therefore, the present invention provides an adsorbent box, comprising:
[0056] a first layer consisting of activated carbon;
[0057] a second layer directly in contact with the first layer, the second layer consisting of one or both of hydrated zirconium oxide and zirconium phosphate,
[0058] in:
[0059] The moisture content of the first layer is X wt.%;
[0060] The moisture content of the second layer is Y wt.%;
[0061] The difference in moisture content between the first layer and the second layer is less than or equal to 8 wt.%.
[0062] In embodiments of the present invention, the word "comprising" may be interpreted as requiring the features mentioned, but not limiting the presence of other features. Alternatively, the word "comprising" may also refer to the case where only components / features that are present are listed (for example, the word "comprising" may be replaced by the phrase "consisting of" or "consisting essentially of". It is expressly contemplated that both broader and narrower interpretations may apply to all aspects and embodiments of the present invention. In other words, the word "comprising" and its synonyms may be replaced by the phrase "consisting of" or the phrase "consisting essentially of" or their synonyms, and vice versa.
[0063] As used herein, "sorbent cartridge" refers to a container composed of a material capable of removing toxins from a dialysate, i.e., a renal dialysis sorbent cartridge. More specifically, the renal dialysis sorbent cartridge can be used for peritoneal dialysis.
[0064] The adsorbent box of the present invention comprises at least two layers: a first layer composed of activated carbon and a second layer composed of one or both of hydrated zirconium oxide and zirconium phosphate. The second layer is in direct contact with the first layer.
[0065] The first layer and the second layer both have a certain water content, which is represented by X wt.% and Y wt.% respectively. The difference between the water content of the first layer and the second layer is less than or equal to 8 wt.%. In other words, the difference between X and Y is less than or equal to 8.
[0066] Here, the "water content" of each layer refers to the amount of liquid adsorbed or absorbed in the solid components of the corresponding layer. Usually, the water content mainly refers to water, but other liquids may also constitute a part of the total water content. In certain embodiments of the present invention that may be mentioned herein, the water content of a layer may refer to the water content of the layer. In certain embodiments of the present invention that may be mentioned herein, the water content of a layer is the same as the loss on drying of the layer, such as the loss on drying of the layer at 210°C (such as the result measured at 210°C using a Radwag MA200.3Y moisture analyzer). For example, a solid sample (such as 1-2g) can be placed in a Radwag MA200.3Y moisture analyzer and a loss on drying experiment can be performed at 210°C. The experiment involves heating the sample at 210°C until the instrument measures the loss on drying value.
[0067] In certain embodiments of the present invention, the second layer may be composed of hydrous zirconium oxide. The sorbent cartridge may include a third layer composed of zirconium phosphate. Figure 1 A schematic diagram of one of the embodiments is shown, wherein 101 represents activated carbon, 102 represents hydrated zirconium oxide, and 103 represents zirconium phosphate.
[0068] In certain embodiments of the present invention, the second layer may be composed of zirconium phosphate. The sorbent cartridge may include a third layer composed of hydrated zirconium oxide. Figure 1 , where layers 102 and 103 are reversed.
[0069] The third layer (if present) has a moisture content of Z wt.% and may be in direct contact with the second layer. In these embodiments of the invention, the difference in moisture content between the second and third layers may be less than or equal to 8 wt.%. In other words, the difference between Y and Z may be less than or equal to 8.
[0070] In an embodiment of the present invention, the sorbent cartridge comprises a separate zirconium phosphate layer and a hydrated zirconium oxide layer. When the sorbent cartridge is in use, the dialysate first passes through the zirconium phosphate layer and then passes through the hydrated zirconium oxide layer. Figure 1 In the embodiment shown, the dialysate will first pass through layer 103, then through layer 102, and finally through layer 101. If the order of layers 102 and 103 is reversed so that zirconium phosphate is the middle layer, the dialysate will first pass through the activated carbon layer, then through the zirconium phosphate middle layer, and finally through the hydrated zirconium oxide layer.
[0071] In certain embodiments of the present invention that may be referred to herein, the second layer may be comprised of hydrous zirconium oxide and zirconium phosphate (eg, a homogeneous mixture of hydrous zirconium oxide and zirconium phosphate). Figure 2 A schematic diagram of this embodiment is shown, wherein 201 represents activated carbon, and 202 represents hydrous zirconium oxide and zirconium phosphate layers.
[0072] In embodiments of the present invention that may be mentioned herein, the difference in moisture content between adjacent layers (such as the first layer and the second layer, or the second layer and the third layer) may be less than or equal to 8 wt.%. In other embodiments of the present invention that may be mentioned herein, the difference in moisture content between adjacent layers may be less than or equal to 5 wt.%, 4 wt.% or 3 wt.%. It will be appreciated by those skilled in the art that these values also apply to the difference in moisture content between the first layer and the second layer and between the second layer and the third layer. All possible combinations of moisture content differences of the layers are explicitly considered herein.
[0073] In an embodiment of the present invention, the second layer is composed of one of zirconium phosphate and hydrated zirconium oxide, and the third layer is composed of the other of zirconium phosphate and hydrated zirconium oxide, the difference between the following two items:
[0074] the moisture content of the first layer;
[0075] The weighted average of the moisture content of the second and third layers,
[0076] The weighted average of the moisture content of the second and third layers is based on the mass of hydrated zirconium oxide and the mass of zirconium phosphate in these layers.
[0077] In certain embodiments of the invention that may be mentioned herein, the difference in water content between the first layer and the second layer is small, which can be achieved by utilizing an activated carbon layer (first layer) having a higher water content than commercially available activated carbon. By increasing the water content of the activated carbon, a small difference in water content between the layers can be achieved without significantly reducing the water content of the hydrated zirconium oxide and zirconium phosphate. In this way, the water content of the boundaries of the layers can be kept similar without affecting the ion exchange capacity of the ion exchange compounds (hydrated zirconium oxide and zirconium phosphate). In contrast, if the water content of the hydrated zirconium oxide and zirconium phosphate is too low, the ion exchange capacity may be affected, as shown in Table 1 above.
[0078] In certain embodiments of the present invention, the water content of the first layer may be between 20-35wt.%, for example, between 23-30wt.% or between 25-35wt.%. It will be appreciated by those skilled in the art that when the water content of the first layer meets the requirements of the present embodiment, the difference in water content between the first layer and the second layer is less than or equal to 8wt.% (for example, the water content of the second layer may be between 12-43wt.%). In certain aspects of the embodiments of the present invention, the water content of the second layer may also be between 20-35wt.%, for example, between 23-30wt.% or between 25-35wt.%.
[0079] In certain embodiments of the present invention, the water content of the second layer may be between 20-35wt.%, for example, between 23-30wt.% or between 25-35wt.%. It will be appreciated by those skilled in the art that when the water content of the second layer meets the requirements of the present embodiment, the difference in water content between the first layer and the second layer is less than or equal to 8wt.% (for example, the water content of the first layer may be between 12-43wt.%). In certain aspects of the embodiments of the present invention, the water content of the first layer may also be between 20-35wt.%, for example, between 23-30wt.% or between 25-35wt.%.
[0080] In certain embodiments of the present invention that may be mentioned herein, when the third layer is present, its water content may be between 20-35wt.%, and may be selected to be between 23-30wt.%, or between 25-35wt.%. It will be appreciated by those skilled in the art that when the water content of the third layer meets the requirements of this embodiment, the difference in water content between the second layer and the third layer is less than or equal to 8wt.% (for example, the water content of the second layer may be between 12-43wt.%). In certain aspects of the embodiments of the present invention, the water content of the second layer may also be between 20-35wt.%, for example, between 23-30wt.% or between 25-35wt.%.
[0081] In the embodiment of the present invention of separate zirconium phosphate and hydrous zirconium oxide layers, the water content of the hydrous zirconium oxide layer may be between 25-35 wt.%.
[0082] In an embodiment of the present invention, the second layer consists of zirconium phosphate and hydrated zirconium oxide (e.g., a homogeneous mixture of zirconium phosphate and hydrated zirconium oxide), wherein the water content of the second layer (consisting of a homogeneous mixture of hydrated zirconium oxide and zirconium phosphate) may be between 23-30 wt.%.
[0083] The above mentioned wt.% values are believed to be beneficial because they avoid interlayer cracking or separation while providing sufficient water content to allow the zirconium phosphate and hydrated zirconium oxide to achieve effective ion exchange during dialysis.
[0084] It will be appreciated by those skilled in the art that the adsorbent cartridge of the present invention may include additional layers. For example, in certain embodiments of the present invention that may be mentioned herein, the adsorbent cartridge may include a urease layer consisting of immobilized urease. In certain embodiments, the water content of the urease layer may be between 17-27 wt.%, such as between 19-25 wt.%, such as between 20-24 wt.%.
[0085] In the embodiment of the present invention where a urease layer is present, the urease layer may be in direct contact with at least one of the first layer, the second layer, and the third layer (if any). The difference in moisture content between the urease layer and the other layers in direct contact therewith may be less than or equal to 8 wt.%, such as less than or equal to 5 wt.%, less than or equal to 4 wt.%, or less than or equal to 3 wt.%.
[0086] In embodiments of the invention where a urease layer is present, the optimal location for the urease layer is in an upstream layer compared to the layer composed of zirconium phosphate. This is because the urease layer produces ammonia, which should be removed from the liquid passing through the adsorbent to prevent it from being transmitted to the patient. Ammonia can be removed by zirconium phosphate, so the optimal location for the urease layer is upstream of the zirconium phosphate layer.
[0087] The present invention is illustrated by the following examples which are not to be construed as limiting.
[0088] Examples
[0089] Abbreviations:
[0090] AC = Activated Carbon
[0091] ZP = Zirconium Phosphate
[0092] HZO=Hydrated Zirconium Oxide
[0093] LOD = Loss on Drying
[0094] All materials were obtained from commercial suppliers and used without further purification.
[0095] General approach
[0096] In the following examples and comparative examples, layered adsorbents were prepared according to the following method.
[0097] Layer 1 (activated carbon) was obtained from a commercial supplier with a loss on drying (LOD) of 8-10%.
[0098] The 1 layer (activated carbon) with a drying loss of 20-25% was prepared by adjusting the water content of the activated carbon. Deionized water was added to the activated carbon with a drying loss of 8%, and mixed with an overhead stirrer at 25°C for 5-10 minutes. The drying loss was then measured at 210°C using a Radwag MA200.3Y moisture analyzer.
[0099] To obtain activated carbon with a drying loss of 25% from 100 g of activated carbon with a drying loss of 8%, the following formula was used:
[0100]
[0101] Where x = the amount of water (g) that needs to be added to 100g of activated carbon with a drying loss of 8% to produce activated carbon with a drying loss of 25%
[0102] The zirconium phosphate and hydrated zirconium oxide layers were prepared by mixing specified amounts of zirconium phosphate and hydrated zirconium oxide. Zirconium phosphate with a loss on drying of 20-25% and hydrated zirconium oxide with a loss on drying of 35-40% were obtained from the same commercial supplier. The hydrated zirconium oxide with a loss on drying of 25% was obtained by heating commercially available hydrated zirconium oxide with a known loss on drying until the desired loss was reached.
[0103] The drying loss analysis is as follows: a solid sample (e.g. 1-2 g) is placed in a Radwag MA200.3Y moisture analyzer and a drying loss experiment is performed at 210° C. The experiment involves heating the sample at 210° C. until the drying loss is measured by the instrument.
[0104] Comparative Example 1
[0105] The layered preparation of the double-layer comparative adsorbent 1 is shown in Table 2 below.
[0106]
[0107] Table 2
[0108] Comparative adsorbent 1 is a conventional adsorbent in which the layers have typical water contents known in the art. The difference in water content between layer 1 and layer 2 is about 12%.
[0109] Figure 3 The photographs show the results of a 9-week storage test under ambient conditions / room temperature, wherein (A) is the comparative adsorbent 1 at week 0, and (B) is the comparative adsorbent 1 at week 9. The black portion in the figure is the activated carbon layer, and the white portion is the zirconium phosphate / hydrated zirconium oxide layer.
[0110] After 9 weeks, obvious cracks and unevenness appeared between the layers as shown by the dotted lines. Therefore, Comparative Adsorbent 1 was not storage stable over a period of 9 weeks.
[0111] Example 1
[0112] The layered preparation of the double-layer adsorbent 1 is shown in Table 3 below.
[0113]
[0114] Table 3
[0115] Adsorbent 1 is made according to the present invention, and the difference in water content between the two layers is minimal. The difference in water content between the first layer and the second layer is between 0-5%.
[0116] Figure 4 The photographs show the results of a 9-week storage test under ambient conditions / room temperature, wherein (A) is Adsorbent 1 at week 0, and (B) is Adsorbent 1 at week 9. The black portion in the figure is the activated carbon layer, and the white portion is the zirconium phosphate / hydrated zirconium oxide layer.
[0117] After 9 weeks, no obvious cracks or other unevenness appeared between the layers.
[0118] Therefore, it was shown that the storage stability of adsorbent 1 under ambient conditions could reach at least 9 weeks.
[0119] Comparative Example 2
[0120] Comparative adsorbent 2 was prepared according to Table 4 below.
[0121]
[0122] Table 4
[0123] The difference in moisture content between layer 1 and layer 2 is about 17-20%
[0124] Figure 5 The photographs show the results of an 8-week storage test under ambient conditions / room temperature. (A) is the adsorbent cartridge at 2 weeks, (B) is the adsorbent cartridge at 4 weeks, and (C) is the adsorbent cartridge at 8 weeks. The black portion in the figure is the activated carbon layer, and the white portion is the zirconium phosphate / hydrated zirconium oxide layer.
[0125] After 2 weeks, a defect could be seen extending from the boundary between layer 1 and layer 2 towards layer 2 (zirconium phosphate + hydrous zirconium oxide), showing a different water content and appearance. The area of the defect continued to increase during the 8-week test period. Figure 4 The dotted lines in FIG. 3 show the defect boundaries at each time period.
[0126] Therefore, Comparative Adsorbent 2 could not be stably stored for 2 weeks, let alone 8 weeks.
[0127] Example 2
[0128] Adsorbent 2 was prepared according to Table 5 below.
[0129]
[0130]
[0131] Table 5
[0132] The difference in moisture content between layer 1 and layer 2 is about 1-4%.
[0133] Figure 6 The photographs show the results of the 8-week storage test under ambient conditions / room temperature. (A) is the adsorbent cartridge at 2 weeks, (B) is the adsorbent cartridge at 4 weeks, and (C) is the adsorbent cartridge at 8 weeks. The black portion in the figure is the activated carbon layer, and the white portion is the zirconium phosphate / hydrated zirconium oxide layer.
[0134] During the 8-week test period, no defects, separation or cracks between the layers were found.
[0135] Therefore, Adsorbent 2 can be stored stably under ambient conditions for at least 8 weeks.
[0136] The above-mentioned embodiments and comparative examples show that the sorbent cartridge of the present invention has excellent long-term storage stability, and its stability is improved compared with the conventional dialysis sorbent cartridge, since the conventional dialysis sorbent cartridge cannot control the difference in water content at the boundaries of each layer.
Claims
1. An adsorbent box, comprising a first layer consisting of activated carbon; a second layer directly in contact with the first layer, the second layer consisting of one or both of hydrated zirconium oxide and zirconium phosphate, in: The moisture content of the first layer is X wt.%; The moisture content of the second layer is Y wt.%; The difference in moisture content between the first layer and the second layer is less than or equal to 8 wt.%.
2. The sorbent cartridge of claim 1, wherein the second layer is composed of hydrated zirconium oxide and zirconium phosphate.
3. The sorbent cartridge of claim 2, wherein the second layer is comprised of a homogeneous mixture of hydrous zirconium oxide and zirconium phosphate.
4. The adsorbent cartridge according to claim 1, wherein The second layer is composed of one of zirconium phosphate and hydrated zirconium oxide; The adsorbent box also includes a third layer composed of another zirconium phosphate and hydrated zirconium oxide that are not present in the second layer; The moisture content of the third layer is Z wt.%; The difference in moisture content between the second layer and the third layer is less than or equal to 8 wt.%.
5. The adsorbent box according to claim 4 is configured so that the dialysate first passes through the zirconium phosphate layer and then passes through the hydrated zirconium oxide layer when in use.
6. The sorbent cartridge according to any one of the preceding claims, wherein the difference in moisture content between the first layer and the second layer is less than or equal to 5 wt.%.
7. The adsorbent box according to claim 6, wherein the difference in moisture content between the first layer and the second layer is less than or equal to 4 wt.%, and optionally less than or equal to 3 wt.%.
8. The sorbent cartridge according to claim 4 or 5, wherein the difference in moisture content between the second layer and the third layer is less than or equal to 5 wt.%.
9. The adsorbent cartridge according to claim 8, wherein the difference in moisture content between the second layer and the third layer is less than or equal to 4 wt.%, and optionally less than or equal to 3 wt.%.
10. The sorbent cartridge of any one of claims 4, 5, 8 and 9, wherein the difference between: the moisture content of the first layer; The weighted average of the moisture content of the second and third layers, Less than or equal to 8wt.%, preferably less than or equal to 5wt.%, more preferably less than or equal to 4wt.%, for example less than or equal to 3wt.%, in, The weighted average of the moisture contents of the second layer and the third layer is based on the mass of hydrated zirconium oxide and the mass of zirconium phosphate.
11. The sorbent cartridge according to any one of the preceding claims, wherein the moisture content of the first layer is between 20-35 wt.%, optionally between 23-30 wt.% or between 25-35 wt.%.
12. The sorbent cartridge according to any one of the preceding claims, wherein the moisture content of the second layer is between 20-35 wt.%, optionally between 23-30 wt.% or between 25-35 wt.%.
13. The sorbent cartridge according to any one of claims 4, 5, 8 to 12, wherein the moisture content of the third layer is between 20-35 wt.%, optionally between 23-30 wt.% or between 25-35 wt.%.
14. The sorbent cartridge according to claim 4 or any one of claims 5 and 8-13 (depending on claim 4), wherein the water content of the hydrous zirconium oxide layer is between 25-35 wt.%.
15. The sorbent cartridge according to claim 3, or any one of claims 6, 7, 11, 12 or 13 (depending on claim 3), wherein: The water content of the second layer (composed of a homogeneous mixture of hydrous zirconium oxide and zirconium phosphate) is between 23-30 wt.%.
16. The sorbent cartridge according to any one of the preceding claims, further comprising a urease layer consisting of immobilized urease.
17. The sorbent cartridge according to claim 16, wherein the water content of the urease layer is between 17-27 wt.%, such as between 19-25 wt.%, such as between 20-24 wt.%.
18. The adsorbent box according to claim 16 or 17, wherein the urease layer is in direct contact with at least one of the first layer, the second layer and the third layer (if any), and the difference in water content between the urease layer and the layers in direct contact therewith is less than or equal to 8 wt.%, such as less than or equal to 5 wt.%, less than or equal to 4 wt.% or less than or equal to 3 wt.%, Optionally, when the sorbent cartridge is in use, it is configured such that the urease layer is located upstream of the zirconium phosphate layer.
19. The sorbent cartridge of any one of the preceding claims, wherein the moisture content of the first layer, the second layer, and the third layer and the urease layer (if present) is determined by loss on drying.
20. The sorbent cartridge according to claim 19, wherein the moisture content of the first layer, the second layer, the third layer and the urease layer (if present) is measured by loss on drying at 180-220°C (optionally about 210°C) using a Radwag MA200.3Y moisture analyzer.